1985
DOI: 10.1083/jcb.101.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemotactic factors and other agents on the amounts of actin and a 65,000-mol-wt protein associated with the cytoskeleton of rabbit and human neutrophils.

Abstract: Stimulation of rabbit neutrophils by the chemotactic factors fMet-Leu-Phe and leukotriene B4, by platelet activating factor, or by arachidonic acid produces a rapid and dosedependent increase in the amounts of actin and of a 65,000-mol-wt protein associated with the cytoskeleton. Phorbol 12-myristate, 13-acetate, the calcium ionophore A23187 in the presence or absence of EGTA, and the fluorescent calcium chelator quin-2 also cause an increase in cytoskeletal actin. The stimulated increases in the cytoskeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…We sought to obtain more direct evidence for such a relationship by measuring respiratory burst oxidase activity in cytoskeleton preparations obtained -from PMA-activated human neutrophils. For our studies, cytoskeleton was prepared by extracting the cells with nonionic detergents using techniques similar to those employed in other laboratories (10)(11)(12). We found that the treatment of whole activated neutrophils with Triton X-100 brought most of the proteins into solution, but left behind an insoluble residue of detergent-resistant cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to obtain more direct evidence for such a relationship by measuring respiratory burst oxidase activity in cytoskeleton preparations obtained -from PMA-activated human neutrophils. For our studies, cytoskeleton was prepared by extracting the cells with nonionic detergents using techniques similar to those employed in other laboratories (10)(11)(12). We found that the treatment of whole activated neutrophils with Triton X-100 brought most of the proteins into solution, but left behind an insoluble residue of detergent-resistant cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…4 ml of this suspension was incubated at 370C for 5 min, then supplemented with 40 ,d PMA solution (20 ,sg/ml in DMSO) and incubated for an additional 2 min at 370C to activate the neutrophils, terminating the reaction by immersion in an ice slurry. The suspension was centrifuged at 100 g for 10 min at 40C, the supernatant discarded, and the cells (total 4 X 107 neutrophils) suspended in 2 ml of Triton inhibitor buffer (10)(11)(12) and incubated at 0°C for 30 min. Next, 0.3 ml of the cell suspension was reserved for measuring total respiratory burst oxidase activity, while 0.…”
mentioning
confidence: 99%
“…The cytoskeletal fraction was isolated by a modification (26) of the procedure reported by Yassin et al (27), which is basically an isotonic extraction in 2% Triton X-100 containing EGTA. For phosphorylation the cytoskeletal fraction containing 0.1 mg of protein was incubated with continuous shaking at 30QC in 0.25 ml of 50 mM sodium borate buffer, pH 7.5, containing 5 mM MgCl2 and 5 ,uM [y-32P]ATP (0.25 mCi/mmol) in the presence of 1.25 units of either protein kinase C or PKC-M.…”
Section: Methodsmentioning
confidence: 99%
“…Human neutrophils (5 x 106 cells per ml) prepared as previously described (22) were incubated at 37°C in 10 mM Hepes, pH 7.4, containing 0.14 M NaCl, 5 mM KCl, and 5 mM glucose, with or without PMA at 10-100 ng/ml, for 10 min. The cells were then cooled at 0°C and collected by centrifugation at 600 x g for 5 min.The cytoskeletal fraction was isolated by a modification (26) of the procedure reported by Yassin et al (27), which is basically an isotonic extraction in 2% Triton X-100 containing EGTA. For phosphorylation the cytoskeletal fraction containing 0.1 mg of protein was incubated with continuous shaking at 30QC in 0.25 ml of 50 mM sodium borate buffer, pH 7.5, containing 5 mM MgCl2 and 5 ,uM [y-32P]ATP (0.25 mCi/mmol) in the presence of 1.25 units of either protein kinase C or PKC-M.…”
mentioning
confidence: 99%
“…The stimulation of PMNs with f-MLP results in a well-characterized biphasic RALS (6,13,16,39,40) and actin (7,8,16,33,(36)(37)(38) response. However, in comparing the data obtained by the two methods, similarities and differences are apparent.…”
Section: Emlpmentioning
confidence: 99%